Handbook of derivatization reactions for HPLC - Lunn, George, 1950- (Wiley, 1998)
"This valuable reference offers fast and convenient access to derivatization reactions for both HPLC and capillary electrophoresis (CE). Covering a wide variety of compounds from pharmaceutical drugs and biological products to industrial contaminants, it is organized first by functional group and then by individual reagents. Techniques for each functional group are described in sufficient detail that the researcher can replicate procedures without reference to the original publicationssaving hours of tedious library research. And because detailed procedures for the same reagent are listed together, it is easy to combine features of different methods and tailor them to fit specific individual requirements."--BOOK JACKET.